Axonal and perikaryal involvement in chronic inflammatory demyelinating polyneuropathy. Issue 6 (1st June 1999) - Nagamatsu, M; Terao, S; Misu, K; Li, M; Hattori, N; Ichimura, M; Sakai, M; Yamamoto, H; Watanabe, H; Riku, S; Ikeda, E; Hata, J; et al.
Abstract : OBJECTIVES: To assess the extent of loss of myelinated nerve fibres and spinal motor neuron loss in chronic inflammatory demyelinating polyneuropathy (CIDP), a clinicopathological study was conducted on biopsied sural nerves and necropsied spinal cords from patients with CIDP. METHODS: The myelinated fibre pathology of 71 biopsied sural nerves and motor neuron pathology of nine necropsied spinal cords at L4 levels in patients with CIDP were quantitatively and immunohistochemically assessed. RESULTS: Myelinated nerve fibre density was significantly diminished to 65.4% of the control values (p <0.0001), correlating inversely with the extent of segmental demyelination and remyelination ( r = −0.43, p < 0.0005) and duration of illness ( r = −0.31, p < 0.01). Numbers of large spinal motor neurons in CIDP were variably but significantly diminished (range from 46.0 to 97.6% of the age matched control value (p < 0.005)), and reactive astrogliosis was evident in the ventral horn in CIDP. The frequency of ventral horn neurons exhibiting central chromatolysis and the accumulation of phosphorylated high molecular weight neurofilament protein was significantly higher in CIDP than in controls (p<0.01 and p<0.05). CONCLUSIONS: The loss of nerve axons and spinal motor neurons is common in CIDP, and extensive in some cases. These neuronal and axonal losses may influence the functional prognosis in CIDP.